(untitled) (CIPEEX, 2026)
This study analyzes the protection of free competition and economic order in the face of the challenges posed by the digital age, focusing on the issue of algorithmic unfair competition. It argues that the automation and opacity of artificial intelligence systems have resulted in a new and covert form of illegality, creating an undue competitive advantage that refers to the invisibility and difficulty of attribution represented by the metaphor of the “black box algorithm.” The paper explores how the legal system, especially the Industrial Property Law (Law No. 9,279/96) and the Law on Crimes Against the Economic Order (Law No. 8,137/90), has gaps in adequately classifying and curbing these new behaviors. It demonstrates that case law, despite already debating the liability of platforms (Themes 987 and 533 of the STF), has not yet made decisive progress on algorithmic manipulation, largely due to the limits of criminal classification and the complex difficulty of proving it. It analyzes the challenge of proving intent and the insufficiency of current criminal classifications. It concludes that overcoming this evidentiary barrier and creating specific legislation—which criminalizes anti-competitive manipulation and regulates high-impact algorithms—are imperative to adapt competition law to the new times and ensure that technology is an instrument of innovation, not abuse of economic power.